From “pueblo pobre” to “pueblo indígena”. Pastoral Aborigen and anthropological knowledge in the Chaco region in Argentina (1970-1985) (Quinto Sol, 2016)
The article examines the deployment of social networks of pastoral aborigen in the Argentinean Chaco region between 1970 and 1985. It describes the structuring process of these networks and analyzes the relations that pastoral aborigen agents held with anthropologists and anthropological knowledge. The analysis is based on files –which the author has had access to– located in what functioned as a regional training center. The paper suggests that, being Development an hegemonic paradigm in the 1960s, it created conditions of possibility for the deployment of these networks. Furthermore, the article argues that ethnic markings on populationsin which the pastoral agents were involved with were mediated by an incorporation of different anthropological knowledge. In this regard, people first assumed as “the poorest of the poor” gradually became named as “communities” and pueblos aborígenes.
Keywords: Pastoral aborigen; anthropology; Chaco region; indigenism